2014
DOI: 10.4049/jimmunol.1301513
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Efficacy of Suppressing the JAK/STAT Pathway in Multiple Models of Experimental Autoimmune Encephalomyelitis

Abstract: Pathogenic T helper cells and myeloid cells are involved in the pathogenesis of Multiple Sclerosis (MS) and Experimental Autoimmune Encephalomyelitis (EAE), an animal model of MS. The JAK/STAT pathway is utilized by numerous cytokines for signaling, and is critical for development, regulation and termination of immune responses. Dysregulation of the JAK/STAT pathway has pathological implications in autoimmune and neuroinflammatory diseases. Many of the cytokines involved in MS/EAE, including IL-6, IL-12, IL-23… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
95
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 127 publications
(101 citation statements)
references
References 70 publications
5
95
0
1
Order By: Relevance
“…Active EAE was induced as previously described (3,34). Eight-to 12-wkold SOCS3 fl/fl or LysMCre-SOCS3 fl/fl mice were immunized s.c. with 100 mg MOG emulsified in CFA (supplemented with 2 mg/ml Mycobacterium tuberculosis) and injected i.p.…”
Section: Eae Induction and Assessmentmentioning
confidence: 99%
“…Active EAE was induced as previously described (3,34). Eight-to 12-wkold SOCS3 fl/fl or LysMCre-SOCS3 fl/fl mice were immunized s.c. with 100 mg MOG emulsified in CFA (supplemented with 2 mg/ml Mycobacterium tuberculosis) and injected i.p.…”
Section: Eae Induction and Assessmentmentioning
confidence: 99%
“…Many of the MS-promoting cytokines such as IL-1β, TNF-α and especially that of IL-6 and IL-12 either signal through or induce JAK/STAT signaling molecules [84]. Studies have implicated the JAK/STAT axis in regulating clinical manifestations of EAE [85]. JAK inhibitors produced promising result in some inflammatory diseases [86] [87].…”
Section: /15mentioning
confidence: 99%
“…JAK inhibitors produced promising result in some inflammatory diseases [86] [87]. JAK inhibitors interrupt cytokine signaling; consequently, break the inflammatory process, a useful process in MS and EAE [85] (Figure 2). Indeed, previous study reported tyrphostin B42, a JAK2 inhibitor; ameliorate EAE [84].…”
Section: /15mentioning
confidence: 99%
“…Thus, inhibition or hyper activation of the JAK / STAT pathway may have therapeutic benefit for several immune-mediated chronic diseases [4]. In 50% to 60% of patients with primary myelofibrosis, a gain-offunction acquired somatic mutation is present in the JAK2 gene.…”
mentioning
confidence: 99%
“…In experimental autoimmune encephalomyelitis (EAE), a rodent model of multiple sclerosis, treatment with AZD1480 decreases disease severity by inhibiting JAK / STAT activation in the brain and reducing expression of proinflammatory cytokines and chemokines [4]. In rheumatoid arthritis patients, Tofacitinib, a JAK inhibitor, has been shown to improve joint symptoms and reduce joint damage in phase 3 trials [8].…”
mentioning
confidence: 99%